A dual expression plasmid with Microcin B17 compatible with both prokaryotic and mammalian systems - Agnieszka M. Murakami; Katsuhiro Nagatomo; Hiroshi Koda; Yasutaka Niwa; Manabu Murakami (MethodsX)
Proteic plasmid addiction systems, such as the control of cell death (Ccd), have been used for efficient plasmid DNA recombination. The CcdB toxin, which has a relatively long sequence of 309 bp, has been the predominant choice for this purpose. However, the need for shorter peptide toxins has emerged. In this study, we evaluated the utility of microcin B17 (MccB17), a peptide consisting of 43 amino acids, in promoting DNA recombination within pgMAX-II, a dual expression plasmid for both prokaryotic and mammalian systems. The insertion of the α-peptide gene from lacZ (α-complementation) demonstrated highly efficient cloning of external DNA in the pgMAX-II/MccB17 plasmid. In both E. coli and mammalian cells, the pgMAX-II/MccB17 plasmid effectively facilitated the expression of the DsRed fluorescent protein gene. The results indicate that the novel pgMAX-II/MccB17 plasmid supports efficient and straightforward subcloning of external genes, achieving dual expression in both prokaryotic (E. coli) and mammalian systems. This suggests its broad applicability as a versatile dual-expression plasmid. • The short toxin peptide gene, MccB17, became available. • MccB17 showed potential for efficient DNA recombination similar to CcdB. • Using MccB17, we successfully established a dual expression plasmid that functions effectively in both prokaryotic and mammalian cells.